Managing of Three Tasks Teacher in Higher Education: Based on Henry Mintzberg Book “Managing” - Latief, Suryawahyuni; Hendrayani, Santi; Samsuddin, Samsuddin (Jurnal Literasiologi, 2024)
This article uses a narrative research approach, with a type of personal narrative research based on Henry Mintzberg's managing book. In writing this article, I focused on the concept of managing and the style of managing. The focus that has been established in writing as a guide for authors in narrating the topic of the managing book according to personal experience, to then potentially be a new field of research and expand the understanding of managing in the study of leadership, management, and organization.